Lessons learned from a state-funded workplace literacy program - Kevin Hollenbeck; Bridget Timmeney (W.E. Upjohn Institute for Employment Research, 2009)
Findings from an evaluation of a workplace literacy program funded by the State of Indiana are presented. Working with employers, providers were given considerable latitude to design their own training regimens. The state awarded certificates to workers who achieved certain levels of proficiency in reading, math, critical thinking, problem solving (assessed by CASAS), and computer literacy (certified by IC3). The evaluation relied on qualitative and quantitative data. Multiple site visits were undertaken and a survey of participants (n = 1800), learning gains, and earnings histories were quantitatively analyzed. Key findings include a significant interest in college attendance by incumbent workers, higher-than-expected levels of literacy in pre-assessments, little reliance on contextualization, and the importance of a program champion and supervisory support at workplaces. Business return was not formally measured, but employers and workers reported significant morale gains and frequent productivity gains.
Keywords: J24; I21; I38; 330